2018
DOI: 10.1021/jacs.8b00131
|View full text |Cite
|
Sign up to set email alerts
|

Helical Rod-like Phenylene Cages via Ruthenium Catalyzed Diol-Diene Benzannulation: A Cord of Three Strands

Abstract: p-Bromo-terminated oligo(p-phenylenevinylenes) emanating from a 1,3,5-benzene core are dihydroxylated and subjected to ruthenium catalyzed diol-diene benzannulation to form tripodal oligo(phenylenes). Copper- or nickel-mediated 3-fold reductive biaryl homocoupling delivers a series of triple-stranded phenylene cages of helical rod-like topology bearing 14, 17, and 20 benzene rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…[26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties. They exhibit rich stereochemical behavior, with both homochiral D 3symmetric and heterochiral C 2 -symmetric diastereomers distinguishable by NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties. They exhibit rich stereochemical behavior, with both homochiral D 3symmetric and heterochiral C 2 -symmetric diastereomers distinguishable by NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In order to achieve this synthesis,overcoming molecular strain is crucial. [2] In this synthesis,t he reductive aromatization can overcome the molecular strain to produce CPPs.I ndependently,Itami reported the synthesis of [12]CPP by the multiple coupling reactions followed by oxidative aromatization of cyclohexane template B. [2] In this synthesis,t he reductive aromatization can overcome the molecular strain to produce CPPs.I ndependently,Itami reported the synthesis of [12]CPP by the multiple coupling reactions followed by oxidative aromatization of cyclohexane template B.…”
mentioning
confidence: 99%
“…[10] Independently, Yamago reported the synthesis of cage G,p ossessing four trisubstituted benzene units,v ia the formation of an octahe- dral platinum complex followed by reductive elimination (Figure 1, bottom right). [12] In this paper,w ed isclose the synthesis of the smallest spherical carbon nanocage so far, [2.2.2]carbon nanocage 1, through the cationic rhodium(I)/H 8 -binap complex-catalyzed regioselective intermolecular homo-cyclotrimerization of terminal alkynes [13][14][15] followed by the triple Suzuki-Miyaura cross-couplings with 1,3,5-triborylbenzene and reductive aromatization of template A (Figure 1, bottom left). [12] In this paper,w ed isclose the synthesis of the smallest spherical carbon nanocage so far, [2.2.2]carbon nanocage 1, through the cationic rhodium(I)/H 8 -binap complex-catalyzed regioselective intermolecular homo-cyclotrimerization of terminal alkynes [13][14][15] followed by the triple Suzuki-Miyaura cross-couplings with 1,3,5-triborylbenzene and reductive aromatization of template A (Figure 1, bottom left).…”
mentioning
confidence: 99%
See 2 more Smart Citations